A Correlational Study of TPACK, Grade and English Language Learning Outcomes of Pre-Service Teachers in West Nusa Tenggara - Lalu Naufaldi Amri; Nanang Zubaidi; Yek Amin Aziz; Husnawadi (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The present study investigated the correlation between TPACK, Grade and English language learning outcomes of Pre-Service Teachers in West Nusa Tenggara. Furthermore, this study's primary purpose is to identify whether there is a significant correlation between TPACK level and grades and its correlation with ELLO. This study is quantitative with a correlational design. The participants were 214 pre-service EFL teachers, determined using stratified sampling. The data were analyzed using SPSS version 24 to determine the TPACK level's correlation with grades and ELLO. Most Pre-service EFL teachers have moderate TPACK grades, and ELLO was given the respective Mode scores M= 3. Further analysis demonstrates a significant correlation between TPACK, grades, and ELLO. This finding encapsulates that the English Study Program in West Nusa Tenggara has prepared the student teachers' TPACK level properly. Furthermore, the results of this study also suggest that the TPACK levels of the EFL pre-service teachers are significantly correlated with their grades and ELLO.